Mental health and Menopause: Understanding women’s mental health in reproductive stage transition - Mrs. Kiruthigadharan (Tamil Psychiatry Journal, 2025)
The reproductive period of women begins with puberty and ends with menopause. The moment when a woman's reproductive period ends is called menopause. During menopause, a woman's ovarian function gradually decreases and eventually stops completely. These menopausal changes occur in stages, not in a day or a few weeks, but over several months. Just as the sun rises and sets slowly, so do the changes caused by menopause slowly come and go, ending a person's life. These menopausal changes not only affect the reproductive organs, but also cause changes in other non-reproductive organs. It is during this period that the menstrual cycle ends and the ovaries stop producing eggs. During menopause female hormones, such as oestrogen and progesterone, decrease. This causes many changes in woman's body and mind. This article discusses in detail the various physiological and emotional changes happening in a woman undergoing menopause and their impact on the woman’s interpersonal and social life. It also discusses the non- pharmacological treatment modalities for perimenopausal syndrome including Neuro-linguistic program NLP therapy.